Malcolm Ross and the New Canadian Library:: Making It Real or Making a Difference? - Groening, Laura (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2000)
The conservative nature of the New Canadian Library as a whole has been accepted as a given; a growing interest in multicultural literature is cited as something that has developed in opposition to the canon that the NCL supposedly instituted. Smaro Kamboureli's anthology of multicultural literature, Making a Difference, claims that all "the contributors, by virtue of their race and ethnicity, belong to the manifold 'margins' that the Canadian dominant society has historically devised" (2). Nevertheless, all but one of Kamboureli's non-contemporary writers have been included in the NCL. Malcolm Ross remembers his goal in setting up the NCL list as an enterprise not in canon-making, but in putting before the Canadian reading public as many texts as he could find that showcased regional and ethnic diversity. That Ross is not celebrated for his contribution to the national literature but, rather, is relegated to a past Robert Lecker dismisses as narrow and materialistic because of his work, and Kamboureli defines as narrow and ethnocentric in spite of his work, is a travesty of cultural history. The reading of the New Canadian Library as a "classic deal," as an institution of canon formation primarily defined by economic interests, is one more colonial act of disparaging Canadian culture.